Declining interest in general surgical training – Challenging misconceptions and improving access at undergraduate level. (April 2019) - Thomas, Amal; Murtaza, Aasim Nisar; Michael Spiers, Harry Victor; Zargaran, Alexander; Turki, Mohammed; Mathur, Jai; Fukui, Akiko; Zargaran, David; Khan, Omar
Abstract: Background: In recent years, general surgery has faced a decline in applicants for postgraduate training. The St. George's Surgical Society hosted a national surgical conference with an aim to explore the reasons for the decline and to investigate the effectiveness of a one-day intervention on students' perceptions of general surgery and surgical skills. Materials and methods: The conference took place on 20th January 2018 at St. George's, University of London. During the conference, medical students received lectures on "careers in surgery" and small-group workshops introducing students to simulation-based laparoscopic machines. Delegates were invited to complete before and after questionnaires looking at various domains; (1) Perceptions of general surgery, (2) Simulation skills, and (3) Usefulness of the day. Results: There were significant impacts on student perceptions of the speciality such as increases in the views that "general surgery contained the opportunities for personal and professional development" (26%, p = 0.04), and of "general surgery as a rewarding speciality" (26%, p = 0.05). There were also negative changes such as an increase in the perception that "general surgery is female unfriendly" (+32%, p = 0.01). There were positive findings in all aspects relating to the use of laparoscopic simulation. Discussion: The challenges faced in improving access to general surgery has been highlighted. More importantly the benefits of a one day intervention in addressing misconceptions and improving knowledge was seen. This study also shows the benefits of simulation teaching in the undergraduate curriculum. Conclusion: The intervention has improved the perceptions on general surgery, surgical skills and knowledge and provided a platform for engaging students and clinicians. Highlights: After the conference, delegates were more likely to look at general surgery in a positive light. The perception of surgery being female unfriendly had risen despite a female surgeon led event. Increased view that surgery contained opportunities for personal and professional development. Increased positive perception and decreased negative perceptions of general surgery. The solution to the problem of declining applicants to general surgery lies in grassroots events.